2010
DOI: 10.1080/19440040903532079
|View full text |Cite
|
Sign up to set email alerts
|

Total arsenic, mercury, lead, and cadmium contents in edible dried seaweed in Korea

Abstract: Total arsenic, mercury, lead, and cadmium contents were determined in 426 samples of seaweed sold in Korea in 2007-08. The average concentrations, expressed in mg kg(-1), dry weight, were: total arsenic 17.4 (less than the limit of detection [LOD] to 88.8), Hg 0.01 (from 0.001 to 0.050), lead 0.7 (less than the LOD to 2.7), and cadmium 0.50 (less than the LOD to 2.9). There were differences in mercury, cadmium, and arsenic content in seaweed between different kinds of products and between coastal areas. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 20 publications
5
30
0
Order By: Relevance
“…In general, brown algae have higher arsenic levels than red or green algae (Almela and others ). Other studies found no harmful quantities of heavy metals (Hwang and others ; Smith and others ; Dhaneesh and others ). Little is known about the process of metal bioaccumulation in marine food chains because data on metal concentrations at different trophic levels and their temporal or spatial variation are sparse (Van Netten and others ; Riosmena‐Rodriguez and others ; Akköz and others ).…”
Section: Novel Proteinsmentioning
confidence: 81%
“…In general, brown algae have higher arsenic levels than red or green algae (Almela and others ). Other studies found no harmful quantities of heavy metals (Hwang and others ; Smith and others ; Dhaneesh and others ). Little is known about the process of metal bioaccumulation in marine food chains because data on metal concentrations at different trophic levels and their temporal or spatial variation are sparse (Van Netten and others ; Riosmena‐Rodriguez and others ; Akköz and others ).…”
Section: Novel Proteinsmentioning
confidence: 81%
“…However, in terms of the high exposure level (P97.5), they may be the potential adverse effect on human health. Several studies also claimed that total elemental intake does not appear to pose any threat to the consumers in Italy, South Korea and Spain 13,14,22 , though different safety reference values, such recommended reference dose (RfD) from US EPA and provisional tolerable weekly intake (PTWI) from the Joint FAO/WHO Expert Committee were used for assessment.…”
Section: Resultsmentioning
confidence: 99%
“…For calculating exposure dose, we adopted 5.2 g/capita/day as the consumption of seaweeds in China, which is higher than in Japan for 4 g/adult/day 23 and lower than in South Korea for 8.5 g/adult/day 22 . In addition, it should be noted that the risk assessment on arsenic was not performed because the arsenic species were not analyzed here.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary exposure to a given chemical from an individual food can be determined by multiplying the concentration of the chemical in the food by intake rate. The provisional tolerable weekly intake (PTWI) of As can be calculated using the information provided by Lee et al (2006) and Hwang et al (2010). For example, the weekly intake of As from bryozoans per unit body weight = {∑[As concentration in each sample × mean seaweed intake (g person -1 day -1 )] × 7 days}÷reference body weight = [∑(49 mg kg -1 dry weight × 8.5 g person -1 day -1 ) × 7 days]÷(63.3 kg body weight) = 46 μg kg -1 body weight.…”
Section: Host-pathogen Interactionsmentioning
confidence: 99%